Criminal liability of the Director in case of tax evasion offences - Teliceanu, Viorel-Gabriel (Eximia, 2023)
Tax evasion, which is included in the category of economic and financial offences, essentially consists of all unlawful procedures by means of which natural or legal persons evade taxable income by failing to fulfil their fiscal obligations.Tax evasion offences are mainly based on economic activities carried out by companies, which raises the question of the criminal liability of the statutory Director, de facto Director or the Company. The criminal liability of the natural person does not remove the criminal liability of the legal person, although in the judicial practice, there is a temptation to use the criminal liability of the legal person as a form of strict liability for the act of another. The criminal liability of the legal person includes the actual analysis of the elements of guilt of the legal person.